2020
DOI: 10.1017/edp.2020.1
|View full text |Cite
|
Sign up to set email alerts
|

The relationship among children’s learning disabilities, working memory, and problem behaviours in a classroom setting: Three case studies

Abstract: Over 2.4 million children in the public school system are diagnosed with a learning disability, including dyslexia and developmental dyscalculia. Previous research has shown that some teachers are unaware of the importance of working memory in a student’s academic and social realm and what working memory deficits may look like in the classroom. The relationship between learning disabilities, working memory, and behaviour problems were examined with tailored recommendations for improvement to provide insight fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 37 publications
0
14
0
2
Order By: Relevance
“…The contributions that have already been made by educational and developmental psychology have been wide-ranging and important, but there is further work to be done for educational and developmental psychologists in this space. While there is currently incredible work being produced in the field of educational and developmental psychology, I invite future research to respond to the unprecedented challenges before us (Alloway & Carpenter, 2020;Furlonger et al, 2020;Gindidis et al, 2020;Satici, 2020;Slaten et al, 2020;Spadafora et al, 2020;Zamora et al, 2020;Miller & Berger 2020;Deadman 2020;Frydenberg 2020a;Wilkerson 2020;Frydenberg 2020b). While educational and developmental psychologists are uniquely positioned to help children and young people to cope with stressors and challenges, there is a role for educational and developmental psychologists as a profession to do much more.…”
Section: A Call To Actionmentioning
confidence: 99%
“…The contributions that have already been made by educational and developmental psychology have been wide-ranging and important, but there is further work to be done for educational and developmental psychologists in this space. While there is currently incredible work being produced in the field of educational and developmental psychology, I invite future research to respond to the unprecedented challenges before us (Alloway & Carpenter, 2020;Furlonger et al, 2020;Gindidis et al, 2020;Satici, 2020;Slaten et al, 2020;Spadafora et al, 2020;Zamora et al, 2020;Miller & Berger 2020;Deadman 2020;Frydenberg 2020a;Wilkerson 2020;Frydenberg 2020b). While educational and developmental psychologists are uniquely positioned to help children and young people to cope with stressors and challenges, there is a role for educational and developmental psychologists as a profession to do much more.…”
Section: A Call To Actionmentioning
confidence: 99%
“…This result is in consistent with the previous research findings carried out among this population. [ 23 24 25 26 ] Prior studies have tried to explore the neural and cognitive basis of learning disability, and it was found that reading disability (dyslexia) is associated with deficit in phonological working memory and central executive functioning. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…WM is one component of the foundational cognitive system outlined in Miller and Maricle’s (2019) model and is responsible for the short-term storage and manipulation of information (Baddeley, 2007a; Engle et al, 1999). WM plays a significant role in the academic environment, given its need in many important typical academic tasks, such as reading (Giofrè et al, 2018; Peng et al, 2018; Raghubar et al, 2010; Swanson, 1999), math (Allen et al, 2021; Gathercole & Pickering, 2000; Geary et al, 2004; Peng et al, 2016; Ramirez et al, 2013; Zheng et al, 2011), and writing (Soto et al, 2021), as these activities require that students use WM to simultaneously retain and process relevant information (Alloway & Alloway, 2010; Alloway & Carpenter, 2020; Brandenburg et al, 2015; Gathercole & Alloway, 2008).…”
Section: Working Memory and Academic Successmentioning
confidence: 99%
“…Much research has established the role of WM in students’ academic success (Alloway & Alloway, 2010; Alloway & Carpenter, 2020; Kyttala et al, 2019; Maehler & Schuchardt, 2016). Word decoding skills, reading comprehension, and mathematical abilities have all been linked to WM processing (Peng et al, 2016, 2018; Swanson, 1999; Zheng et al, 2011).…”
Section: Working Memory and Academic Successmentioning
confidence: 99%